Post-disturbance recovery of forest carbon in a temperate forest landscape under climate change - Dobor, Laura; Hlásny, Tomáš; Rammer, Werner; Barka, Ivan; Trombik, Jiří; Pavlenda, Pavol; Šebeň, Vladimír; Štepánek, Petr; Seidl, Rupert (Agricultural and forest meteorology, 2018)
Disturbances alter composition, structure, and functioning of forest ecosystems, and their legacies persist for decades to centuries. We investigated how temperate forest landscapes may recover their carbon (C) after severe wind and bark beetle disturbance, while being exposed to climate change. We used the forest landscape and disturbance model iLand to quantify (i) the recovery times of the total ecosystem C, (ii) the effect of climate change on C recovery, and (iii) the differential factors contributing to C recovery. We reconstructed a recent disturbance episode (2008-2016) based on Landsat satellite imagery, which affected 39% of the forest area in the 16,000 ha study landscape. We subsequently simulated forest recovery under a continuation of business-asusual management until 2100. Our results indicated that the recovery of the pre-disturbance C stocks (C payback time) was reached 17 years after the end of the disturbance episode. The C stocks of a theoretical undisturbed development trajectory were reached 30 years after the disturbance episode (C sequestration parity). Drier and warmer climates delayed simulated C recovery. Without the fertilizing effect of CO2, C payback times were delayed by 5-9 years, while C parity was not reached within the 21st century. Recovery was accelerated by an enhanced C uptake compared to undisturbed conditions (disturbance legacy sink effect) that persisted for 35 years after the disturbance episode. Future climate could have negative impacts on forest recovery and thus further amplify climate change through C loss from ecosystems, but the effect is strongly contingent on the magnitude and persistence of alleviating CO2 effects. Our modelling study highlights the need to consider both negative and positive effects of disturbance (i.e., C loss immediately after an event vs. enhanced C uptake of the recovering forest) in order to obtain a comprehensive understanding of disturbance effects on the forest C cycle.
Keywords: Central Europe; Legacy sink; CO2 fertilization; Forest carbon sink; Disturbance recovery; Norway spruce